The Quality of Online Relationships in the Time of Covid-19 (Journal of Universal Excellence, 2026)
Research question (RV): Are the parents of adolescents in Slovenia adequately educated regarding the challenges of cyberbullying?Purpose: The purpose of the article is to investigate the area of cyberbullying among Slovenian adolescents in the time of covid-19 through the perception of parents of adolescents in Slovenia.Method: In the article, we used a descriptive method, with the help of which we described the theoretical starting points. In the empirical part of the article, we used a quantitative method, where we used a survey questionnaire that examines the perception of parents of adolescents regarding the possible increase in cyberbullying among adolescents in the time of covid-19.Results: Parents of adolescents from all over Slovenia participated in the research of the article. The statement that, according to the parents of adolescents, the majority of adolescents noticed the occurrence of violence against someone else, but did not take any action, is worrying.Organization: With the help of research, we wanted to examine the frequency of cyberbullying in relation to the time before and during covid-19, which is especially important for organizations (in this case, schools), as they take care of creating a safe and stimulating learning environment, where it is necessary to start with by preventing this form of violence, insofar as we want to achieve the inclusion and physical and psychosocial safety of adolescents.Society: The article examines a socially relevant topic, and due to the fact that covid-19 is a relatively new challenge in the field of virology, the mentioned area is included under the researched area, therefore the present research represents only the beginning of the study of the selected area. The results of the present research can be used by many experts who want to study the topic further, or adolescents, parents and teachers who want to get to know the mentioned area better.Originality: The originality of the article can be seen in the study of a very current social issue, which affects the so far little-researched impact of the covid-19 era on peer violence and cyberbullying among adolescents from the perspective of their parents.Limitations/further research: The limitations of the research are reflected in the limitation of the studied sample, and in addition, incompletely completed questionnaires appeared during the implementation of the survey questionnaire. The research could be expanded to include in-depth interviews among participants, both adolescents and parents as well as education professionals, as school quality is strongly linked to a safe and stimulating learning environment. Further research could also allow us to understand open communication in school, which creates a stronger sense of belonging to the school, because a favourable climate can allow the school to transform into a learning community, which means building a stimulating learning environment characterized by mutual respect and trust both for students and teachers.
Keywords: peer violence; cyberbullying; covid-19; internet; social networks; adolescents; parents